(untitled) (Vallis Aurea, 2023)
Purpose: Sustainable Tourism development in the rural region has become a must which includes the interests of all stakeholders, along with tourism promotion and tourism growth. This study aims to identify the opinion of stakeholders to achieve sustainable rural tourism development. Design: Exploratory Research and descriptive research. Methodology & Approach: Qualitative and Quantitative. Primary data was collected through in-depth interviews and surveys. A structured questionnaire was used as an instrument. The non-probability sampling procedure is used. The sample size of the Community is 262 and of Tour operators is 167. Findings: It has been found that there should be the development of a regional tourism workforce and infrastructure, the introduction of home stay policy, the promotion of a tourism-friendly atmosphere, showcasing Gujarat beyond God and spirituality and the creation of multiple activities in rural areas.